2022
DOI: 10.48550/arxiv.2205.05557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive study of mass ejection and nucleosynthesis in binary neutron star mergers leaving short-lived massive neutron stars

Abstract: By performing a set of numerical relativity simulations for the merger of binary neutron stars with several mass ratios, the properties of ejected matter in dynamical and post-merger phases are investigated for the cases in which the remnant massive neutron star collapses into a black hole in 20 ms after the onset of merger. The dynamical mass ejection is investigated in three-dimensional general relativistic hydrodynamics simulations with an approximate neutrino-radiation transfer. The resulting post-merger s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
(126 reference statements)
1
7
0
Order By: Relevance
“…In this work, we have considered fiducial initial conditions for the outflow, including composition, without allowing for correlations induced by the fact that both the composition and outflows are initialized by BNS mergers. In future work, we will explore self-consistent initialization from merger properties, in particular exploring the effects of binary mass ratio and NS remnant lifetime, which should have significant impact on the ejecta amount and composition [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, we have considered fiducial initial conditions for the outflow, including composition, without allowing for correlations induced by the fact that both the composition and outflows are initialized by BNS mergers. In future work, we will explore self-consistent initialization from merger properties, in particular exploring the effects of binary mass ratio and NS remnant lifetime, which should have significant impact on the ejecta amount and composition [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…cases, the mean energies of electron antineutrinos emitted by the disk are 20-50% higher than the mean energies of electron neutrinos, with values becoming close to one another only before a sharp drop at t ∼ 0.5 s. The drop in mean energies is a consequence of energy luminosities decreasing faster with time than number luminosities as the disk transitions to a radiatively inefficient state with lower temperature and density. Due to enhanced neutrino irradiation and suppressed mass loss through the inner boundary, a longer HMNS lifetime correlates with more mass ejected as well as an overall higher average electron fraction and velocity of the unbound ejecta [49,55,56,78,79], which in turn translates into a lower yield of heavy r-process elements [51,80,81] (Table I). Our model t010-ab00 has a slightly lower average Y e than the prompt BH model due to a relative increase in the ejecta with Y e < 0.25 material (Figure 2)…”
Section: Mass In Bin [M ]mentioning
confidence: 99%
“…Earlier r-process nucleosynthesis studies that adopted either the parametrized BNSM ejecta properties or the outflow trajectories extracted from numerical simulations modeling the post-merger evolution of BNSMs, revealed that a significant amount of actinides with mass fraction X act 10 −3 is only produced in ejecta with Y e 0.2 [47][48][49][50][51][52][53][54][55][56][57][58][59][60]. This can be qualitatively understood from relating the averaged nuclear mass number at the end of the r-process ( A f ) to the averaged initial seed nuclear mass number ( A s ) and the abundance ratio of free neutrons to seed nuclei (R n/s ) before the onset of r-process by…”
Section: Theory Requirements and Nuclear Physics Inputsmentioning
confidence: 99%
“…Broadly, abundance of SLRIs can be measured in three distinct regimes. The first is the measurement of live SLRIs present in the ISM using γ -ray telescopes that detect the emitted γ -rays following radioactive decay of SLRIs such as 26 Al and 60 Fe. Such measurements have been used to directly probe ongoing star formation in the Galaxy [139,140], and can in principle be used to probe the BNSM history as well (see Section 3).…”
Section: Short-lived Radioactive Actinidesmentioning
confidence: 99%